2023
DOI: 10.32604/cmes.2023.021223
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characteristics Measurement Using Computer Vision: A Review

Abstract: Computer vision provides image-based solutions to inspect and investigate the quality of the surface to be measured. For any components to execute their intended functions and operations, surface quality is considered equally significant to dimensional quality. Surface Roughness (Ra) is a widely recognized measure to evaluate and investigate the surface quality of machined parts. Various conventional methods and approaches to measure the surface roughness are not feasible and appropriate in industries claiming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 281 publications
0
7
0
Order By: Relevance
“…Machine vision measurement is a measurement method based on the principle of optical imaging, which collects images through industrial cameras, then extracts feature indices associated with surface roughness parameters from the images, and further predicts the corresponding unknown surface roughness by known image feature index values. [5] Yi et al [6] utilized the strong sensitivity of color information, using the average value of the absolute difference between the red and green components of the statistical image sampling area under an ordinary light source and macro field of view, to establish the correlation between the color difference index and surface roughness, and verified the feasibility of this method through a regression model. Ali et al [7] used the visual system, image processing tools, and the mathematical transformation method of dual orthogonal 2D wavelet transform to evaluate the roughness of the discharge machining (EDM) surface.…”
Section: Introductionmentioning
confidence: 99%
“…Machine vision measurement is a measurement method based on the principle of optical imaging, which collects images through industrial cameras, then extracts feature indices associated with surface roughness parameters from the images, and further predicts the corresponding unknown surface roughness by known image feature index values. [5] Yi et al [6] utilized the strong sensitivity of color information, using the average value of the absolute difference between the red and green components of the statistical image sampling area under an ordinary light source and macro field of view, to establish the correlation between the color difference index and surface roughness, and verified the feasibility of this method through a regression model. Ali et al [7] used the visual system, image processing tools, and the mathematical transformation method of dual orthogonal 2D wavelet transform to evaluate the roughness of the discharge machining (EDM) surface.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that tactile feedback enables fine grip force control of robotic devices (George et al, 2019;Chai et al, 2022) and users' attention allocation (Sklar and Sarter, 1999;Makin et al, 2023) and confers to the users the ability to recognize object size and compliance, with or without visual feedback (Arakeri et al, 2018;George et al, 2019;Chai et al, 2022). However, in terms of human-machine interaction, so far, the 2 types of typical object physical properties, surface roughness and texture, were unable to be delivered to the users through a haptic interface due to the complexity of the surface features (Bajcsy, 1973;Hashmi et al, 2023). A key reason is that the current contact sensors (e.g., pressure/ displacement transducers) cannot identify and differentiate a wide variety of features of the surface roughness and texture.…”
Section: Introductionmentioning
confidence: 99%
“…Machine vision has emerged as the most promising noncontact technique for object detection and image classification by combining cameras, videos, and deep-learning methods (Zhao et al, 2019;Georgiou et al, 2020;Hashmi et al, 2023). Recent representative studies have shown that compared to conventional methods, machine vision-based approaches could better assess the surface quality of machined parts by contactlessly measuring the surface characteristics, i.e., surface roughness, waviness, flatness, surface texture, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid advancement of artificial intelligence technology, machine vision-based defect detection has emerged as a powerful tool for swiftly and accurately identifying product irregularities through non-contact measurements [3,4]. This technology has found widespread adoption within the domain of intelligent manufacturing.…”
Section: Introductionmentioning
confidence: 99%